Knowledge, attitude, and confidence on the use of cognitive behavior therapy for weight loss and maintenance among healthcare providers - Abdul Khaiyom, Jamilah Hanum (2021)
Introduction: Cognitive Behavior Therapy (CBT) has been found to be effective in reducing and maintaining weight loss rather than diet and/or exercise alone. Eventhough CBT remain the cornerstone of obesity treatment and should be included in every weight management program, very limited healthcare providers are trained in using CBT, especially in Malaysia. Current study aims to examine the knowledge, attitude, and confidence on the use of CBT among healthcare providers after they have been exposed in a brief CBT training for weight management.